SYNERGISTIC EFFECT OF MORINGA OLEIFERA ATTENUATES OXIDATIVE STRESS INDUCED APOPTOSIS IN SACCHAROMYCES CEREVISIAE CELLS: EVIDENCE FOR ANTICANCER POTENTIAL. - V.PRASANNA; S.SREELATHA (International Journal of Pharma and Bio Sciences, 2014)
Moringa oleifera is a multipurpose medicinal food of dietary interest known to have health beneficial effects, and has been used as a possible ayurvedic medicine. This study was carried out to investigate the effects of H2O2 induced apoptosis, that measure cellular proliferation, viability, and morphological changes and to investigate if the dietary leaf extract could inhibit the oxidative stress events and the mechanism against the oxidative assaulted biomolecular targets, which simultaneously contributes to the understanding of cellular responses associated. H2O2 induced oxidative stress in yeast cells was assayed with parameters like cell viability, apoptotic morphological and nuclear changes and the antioxidant enzyme levels. The formation of TBARS was also assayed. H2O2 imposed oxidative damage in yeast cells resulted in a sequence of events characteristic of apoptosis, including loss of cell viability, morphological changes and apoptotic nuclear changes. There was a decrease in the levels of antioxidant enzymes, and an increase in the lipid peroxide formation. The presence of the leaf extracts attenuated the oxidative stress and significantly enhanced the levels of antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT). The leaf extracts caused a very significant inhibition of the extent of lipid peroxide formation and further showed a significant hydroxyl radical scavenging activity. The leaf extracts were characterized for the active principles and quercetin glucoside and keampferol rhamnoglucoside were identified in the ethanol leaf extracts. Additionally the leaf extracts also suppressed the effects against H2O2 induced apoptotic cellular changes. These results suggest the valuable use of Moringa oleifera leaves, consumed as leafy vegetable, can provide potential functional nutrients that can help in the prevention of oxidative stress disorders.